Combining Ability and Parent-Offspring Correlation of Maize (Zea may L.) Grain β-Carotene Content with a Complete Diallel - Run LI; Lan-hai XIAO; Jing WANG; Yan-li LU; Ting-zhao RONG; Guang-tang PAN; Yuan-qi WU; Qilin TANG; Hai LAN; Mo-ju CAO (Journal of Integrative Agriculture, 2013)
Vitamin A deficiency has become a worldwide problem. Biofortified foods can potentially be an inexpensive, locally adaptable, and long-term solution to dietary-nutrient deficiency. In order to improve the β-carotene content in maize grain by breeding and minimize vitamin A deficiency, a complete diallel cross was designed with eight inbred lines of maize, and 64 combinations were obtained in this study. The experimental combinations were planted in Yunnan and Sichuan provinces, respectively, with a random complete block design. The β-carotene contents in the grains of the experimental materials were analyzed by high-performance liquid chromatography. Among the tested materials, the effect difference of general combining ability of the β-carotene content was significant; however, the effect difference of the special combining ability and the reciprocal effect were not significant. The β-carotene content of maize grain was not influenced significantly by the cross and the reciprocal cross. There was a significant correlation about the β-carotene content in the maize grains between the F1 and their parents. The combinations with high β-carotene content were obviously influenced by the environment, and the mean value of β-carotene content for the experimental materials planted in Ya'an of Sichuan was higher than that planted in Yuanjiang of Yunnan, with the results being significant at the 0.01 level.